2012
DOI: 10.1111/dom.12027
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor blockade by memantine does not prevent adaptation to recurrent hypoglycaemia in healthy men

Abstract: Attenuation of the endocrine as well as symptomatic counterregulatory response to recurrent hypoglycaemia is not prevented by the NMDA receptor blocker memantine. Our results do not support the view that adaptation to repeated hypoglycaemia relies on NMDA receptor-mediated plastic processes involving long-term potentiation or depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Therefore, patients with type 1 diabetes may develop attenuated glucagon release before IAH develops. This reiterates the importance of the sympathoadrenal response in people with diabetes who have IAH [32].…”
Section: Box 2 Investigating Iah In Humansmentioning
confidence: 65%
“…Therefore, patients with type 1 diabetes may develop attenuated glucagon release before IAH develops. This reiterates the importance of the sympathoadrenal response in people with diabetes who have IAH [32].…”
Section: Box 2 Investigating Iah In Humansmentioning
confidence: 65%
“…Thereafter, insulin was stopped and euglycaemia was re‐established. Repeatedly, blood samples were drawn, and hypoglycaemic symptoms and selective attention (assessed using the Stroop test) were assessed . On the first day at 13:00 h, another hypoglycaemic clamp procedure was performed to achieve repeated exposure to hypoglycaemia.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, insulin was stopped and euglycaemia was re-established. Repeatedly, blood samples were drawn, and hypoglycaemic symptoms and selective attention (assessed using the Stroop test) were assessed [8]. On the first day at 13:00 h, another hypoglycaemic clamp procedure was performed to achieve repeated exposure to whole-blood glucose (conversion factor to plasma glucose: × 1.1), (B) glucose infusion rates, (C) insulin and (D) C-peptide in the placebo (white triangles) and the modafinil condition (black circles: oral administration of 200 mg modafinil at 08:45h on day 2 as indicated by the arrow).…”
Section: Methodsmentioning
confidence: 99%
“…N-methyl D-aspartate (NMDA) is an excitatory glutamate receptor. It has been implicated in long-term potentiation of memory formation and learning 52 . A study in dogs treated with an NMDA antagonist before undergoing insulin- induced hypoglycemia found a reduction in plasma epinephrine and cortisol levels, suggesting that glutamate stimulates the hypothalamic-pituitary-adrenal and the sympathetic-adrenal axis via NMDA channels 53 .…”
Section: Central Approaches For Modulating Haafmentioning
confidence: 99%
“…A study in dogs treated with an NMDA antagonist before undergoing insulin- induced hypoglycemia found a reduction in plasma epinephrine and cortisol levels, suggesting that glutamate stimulates the hypothalamic-pituitary-adrenal and the sympathetic-adrenal axis via NMDA channels 53 . When given an NMDA antagonist for four days prior to undergoing hypoglycemic studies, healthy human subjects demonstrated reduced cortisol, ACTH, epinephrine, norepinephrine, growth hormone and glucagon secretion, which led the authors to conclude that NMDA antagonists are not effective in preventing the hypoglycemic counter-regulatory response 52 . However, a study found that memantine, an NMDA antagonist, caused an increase in counter-regulatory hormones as well as neuroglycopenic symptoms in healthy adults 54 .…”
Section: Central Approaches For Modulating Haafmentioning
confidence: 99%